The Effect of Different Acid Treatments on Shear Bond Strength Between Monolithic Zirconia and Dentin Surface - Oguzhan Gorler; Melih Ulgey (Cumhuriyet University, 2021)
Objective: The aim of this study is to evaluate the effect of dentin surface treatments with citric, tartaric, phosphoric, and boric acids on the bonding strength of monolithic zirconia. Material and Methods: A hundred human molar teeth were randomly divided into subsets (n = 10) based on acid treatment modalities and thermocycling procedure. Monolithic zirconia superstructures were fabricated using CAD/CAM system in the final dimensions of 7 mm in diameter and 3 mm in thickness. After application of acid treatments to dentin surface, shear bond strength test was performed to assess the effectiveness of surface modifications that were also examined using a scanning electron microscope. Results: The study groups were ranked respectively as (citric acid>tartaric acid>phosphoric acid>boric acid>control) for the set of groups without thermocycling and (citric acid>tartaric acid) and (phosphoric acid>boric acid>control) for the set of thermocycling groups (p<0.05) based on highest value. The bonding strength of tartaric acid group was not significantly different from the bonding strength of phosphoric acid group (p>0.05). Conclusion: In both procedures with and without thermal cycling; based on order of efficacy, citric, tartaric, phosphoric, and boric acids were more effective in improving the shear bond strength between monolithic zirconia and dentin surface. The thermal cycling procedure decreased the bonding strength in all the groups.